THE EFFECT OF 3M GAMES (THROWING, CATCHING, AND KICKING) ON EARLY CHILDHOOD GROSS MOTOR SKILLS - Lorenza, Dina; Manto, Manto; Susilo, Ridi Efran (Jurnal Konseling Pendidikan Islam, 2024)
This study investigates the impact of 3M games (Throwing, Catching, and Kicking) on gross motor skills in early childhood in TK Harapan Bunda Empat Lawang. The research method used was an experiment with pretest and posttest control group designs. The sample of this study was 18 randomly selected early childhood children divided into two groups: the control group (n = 9) and the treatment group (n = 9). The treatment group was given an intervention in the form of 3M games for three weeks, while the control group did not receive the intervention. Data was collected using gross motor ability tests before and after the intervention. The results of the data analysis showed a significant improvement in gross motor skills in the treatment group after the 3M game intervention. In contrast, there was no substantial change in the control group. These findings indicate that 3M games effectively improve gross motor skills in early childhood. The implication of this study is the importance of including games involving throwing, catching, and kicking activities in early childhood learning programs to promote gross motor development.